Tree line shifts, changing vegetation assemblages and permafrost dynamics on Galdhøpiggen (Jotunheimen, Norway) over the past ~4400 years - Helen Hallang (The Holocene, 2022)
An environmental reconstruction based on palynological evidence preserved in peat was carried out to examine late-Holocene alpine tree line dynamics in the context of past climatic changes on Galdhøpiggen (Jotunheimen, southern Norway). We analysed a peat core taken from a mire at the present-day tree line (1000 m a.s.l.), c. 450 m downslope from the lower limit of sporadic permafrost. We adopted a combination of commonly used indicators of species’ local presence to reconstruct past vegetation assemblages, such as the relative pollen abundance (%), pollen accumulation rate (PAR), and presence of indicator species. Additionally, fossil pollen from the peat sequence was compared to modern pollen from a surface moss polster to establish a modern analogue. The results were compared with studies covering the late-Holocene climatic changes in the area. The reconstruction demonstrates that a pine-dominated woodland reached above the present-day tree line at c. 4300 cal. yr BP, suggesting a warmer climate suitable for Scots pine ( Pinus sylvestris) growth at this altitude. Scots pine retreated to lower altitudes between c. 3400 and 1700 cal. yr BP, accompanied by the descent of the low-alpine shrub-dominated belt, in response to cooling climatic conditions. The colder period covered c. 1700–170 cal. yr BP, and an open downy birch ( Betula pubescens) woodland became widespread at 1000 m a.s.l., whilst pine remained sparse at this altitude. From c. 170 cal. yr BP onwards, warming allowed pine to re-establish its local presence alongside downy birch at 1000 m a.s.l.